2012
DOI: 10.1074/jbc.m111.297960
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin-induced Ototoxicity Is Mediated by Nitroxidative Modification of Cochlear Proteins Characterized by Nitration of Lmo4

Abstract: Background: Oxidative stress plays a causal role in cisplatin ototoxicity. Results: Cisplatin induces nitration of cochlear proteins that correlate with measures of ototoxicity, and pharmacological inhibition of cochlear protein nitration attenuates ototoxic effects of cisplatin. Conclusion: Nitroxidative modification of cochlear proteins is an important mediator of cisplatin ototoxicity. Significance: Cisplatin-induced nitration of Lmo4 points to novel target genes related to stress responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
57
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(64 citation statements)
references
References 53 publications
(63 reference statements)
7
57
0
Order By: Relevance
“…The ototoxic side effects of cisplatin have been well documented (6,7,9). Consistent with previous reports, a 16 mg/kg dose of cisplatin induced a significant shift in distortion product amplitudes (Fig.…”
Section: Cisplatin-induced Ototoxicitysupporting
confidence: 79%
See 3 more Smart Citations
“…The ototoxic side effects of cisplatin have been well documented (6,7,9). Consistent with previous reports, a 16 mg/kg dose of cisplatin induced a significant shift in distortion product amplitudes (Fig.…”
Section: Cisplatin-induced Ototoxicitysupporting
confidence: 79%
“…The sections were blocked and incubated in anti-SNitroso-Cysteine (1:200) for 2 h followed by 1 h incubation in biotinylated secondary antibody (Vector Laboratories, Burlingame, CA). The sections were then treated with avidin and biotin (Elite ABC-kit; Vector Laboratories) to facilitate immunodetection with 0.05% DAB stain (7).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Like ROS, RNS acts on various targets in the cell, causing cytotoxicity, although its mechanisms are less clear than ROS. In the cochlea, it has been reported that cisplatin nitrates LIM domain only 4 (Lmo4), a transcriptional regulator controlling cell survival and cell death (Jamesdaniel et al., 2012). …”
Section: Cisplatin and Other Platinum Compoundsmentioning
confidence: 99%